There are two boxes with some marbles in them.
If a marble from box-1 is placed into box-2, then box-2 will have double the number of marbles as in box-1. If this process is reversed then both boxes will have same number of marbles.
How many marbles are there in box-1 and box-2 initially?
box-1 with 2 and box-2 with 4 marbles.
box-1 with 2 and box-2 with 3 marbles.
box-1 with 3 and box-2 with 5 marbles.
box-1 with 5 and box-2 with 7 marbles.
Let's assume that the box-1 is having H marbles and box-2 is having C marbles. C + 1 = 2 * (X-1)
C + 1 = 2H - 2
C = 2H - 3
C - 1 = H + 1
C = H + 2
=> 2H - 3 = H + 2
H = 5
=> C = 7
Back To Top